A (t, n) threshold protocol of semi-quantum secret sharing based on single particles - Zhou, Ziyi; Wang, Yifei; Dou, Zhao; Li, Jian; Chen, Xiubo; Li, Lixiang (Frontiers in Physics, 2023)
Semi-quantum secret sharing is an important research issue in quantum cryptography.We combine the practicality of semi-quantum secret sharing protocols and the flexibility of (t, n) threshold quantum secret sharing protocols and propose a (t, n) threshold semi-quantum secret sharing in this paper. Our protocol has some features: (i) it can enable any t of the n participants to recover the secret, which makes our protocol more flexible; (ii) all participants use single particles which are easy to be prepared as quantum resources; (iii) classical participants only need to possess the capability to prepare and insert particles, so they are released from other quantum abilities in our protocol. The proposed protocol has security against most attacks. Also, except decoy particles, all particles are useful to carry the secret message, so the efficiency of the proposed protocol can achieve 100%.